Groups with Maximality Condition for Nonhypercentral Subgroups - Artemovich, O. D. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We obtain a characterization of not finitely generated groups with maximality condition for nonhypercentral (respectively, nonnilpotent) subgroups.